Anne of Green Gables [videorecording (DVD)] - Sullivan, Kevin, 1955-; McDougall, Ian, 1945-2010; Follows, Megan; Dewhurst, Colleen; Farnsworth, Richard, 1920-2000; Montgomery, L. M. (Lucy Maud), 1874-1942 (Sullivan Entertainment, 2002)
An elderly bachelor and his spinster sister adopt an orphan and are mistakenly sent a girl instead of a boy. The orphan, Anne, remains with the couple, moves from one mishap to another, succeeds academically, and finds love.